Physical parameters of the rising kick in taekwon-do - Wasik, J. (Archives of Budo, 2006)
Study aim: To find optimum conditions for performing the twimyo nopi ap chagi jump. Material/methods: This paper contains the theoretical description of the test, from the physical point of view. Results: During the special technique test, the height that the competitor successfully completes, is a sum of 4 heights: the height of the competitor`s center of gravity at the moment of the take-off, the change of the height of the center of gravity of the competitor during the flight, and the difference between the highest point of the center of gravity of the competitor and the height at witch the target is suspended. This is shown by the following formula: H=hto + hfl + ?h + hkl.. Conclusions: The theoretically best angle of take-off for the rising kick is between 65-80 degrees. This angle is necessary to establish the exact spot for the takeoff which will enable the competitor to achieve the best possible result. One must establish this individually for every competitor. The relation between the height of the jump and the force of the takeoff is parabolic; the increase of the takeoff force influences the achieved result.